2007
DOI: 10.3201/eid1308.061560
|View full text |Cite
|
Sign up to set email alerts
|

Babesiasp. EU1 from Roe Deer and Transmission withinIxodes ricinus

Abstract: We report in vitro culture of zoonotic Babesia sp. EU1 from blood samples of roe deer in France. This study provides evidence of transovarial and transstadial transmission of the parasite within Ixodes ricinus, which suggests that this tick could be a vector and reservoir of EU1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
102
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 11 publications
(24 reference statements)
5
102
1
1
Order By: Relevance
“…EU1, and first studies revealed prevalences of up to 30% (Bonnet et al, 2007;Duh et al, 2005b;Hoby et al, 2007b). Interestingly, the parasites seem to have a low virulence in roe deer, and it may be speculated that roe deer acts as a reservoir for the parasite affecting chamois.…”
Section: Discussionmentioning
confidence: 99%
“…EU1, and first studies revealed prevalences of up to 30% (Bonnet et al, 2007;Duh et al, 2005b;Hoby et al, 2007b). Interestingly, the parasites seem to have a low virulence in roe deer, and it may be speculated that roe deer acts as a reservoir for the parasite affecting chamois.…”
Section: Discussionmentioning
confidence: 99%
“…For Babesia sp. EU1, biological evidence of natural transmission by I. ricinus ticks is still lacking; its presence has been assessed only by DNA amplifi cation from whole ticks (4,(6)(7)(8). Therefore, to analyze transmission of zoonotic Babesia spp.…”
mentioning
confidence: 99%
“…Among these pathogens, 2 zoonotic Babesia species have been described in Europe: the well-known cattle parasite Babesia divergens (1) and the more recently reported roe deer parasite Babesia sp. EU1 (2)(3)(4). Biological transmission of B. divergens by I. ricinus ticks has been proven by in vivo experimental infections (5); however, quantitative transmission studies that visualize and quantify sporozoites have never been conducted.…”
mentioning
confidence: 99%
“…EU1; Herwaldt et al 2003), B. divergens, B. capreoli (Enigk et Friedhoff, 1962 and B. odocoilei-like (Duh et al 2005, Bonnet et al 2007a, Malandrin et al 2010, Silaghi et al 2011, Zintl et al 2011, Zanet et al 2014. Babesia venatorum has been identified in roe deer, Capreolus capreolus (Linnaeus) (Duh et al 2005, Bonnet et al 2007a.…”
mentioning
confidence: 99%
“…EU1; Herwaldt et al 2003), B. divergens, B. capreoli (Enigk et Friedhoff, 1962 and B. odocoilei-like (Duh et al 2005, Bonnet et al 2007a, Malandrin et al 2010, Silaghi et al 2011, Zintl et al 2011, Zanet et al 2014. Babesia venatorum has been identified in roe deer, Capreolus capreolus (Linnaeus) (Duh et al 2005, Bonnet et al 2007a. Babesia divergens and B. capreoli have been reported from roe deer, red deer, Cervus elaphus Linnaeus, reindeer, Rangifer tarandus (Linnaeus), alpine chamois, Rupicapra rupicapra (Linnaeus), and alpine ibex, Capra ibex (Linnaeus) (Langton et al 2003, Malandrin et al 2010, Zintl et al 2011, Michel et al 2014.…”
mentioning
confidence: 99%